The Effect of Liquid Organic Fertilizer Made from Gamal Leaves (Gliricidia sepium) on the Growth of Stone Begonia (Begonia sp.) Cuttings - Rahmi; Ramal Yusuf; Nadine; Rahmat; Moh. Ilwan (Postgraduate, University of Mataram, 2026)
Fertilisation is a key factor in improving the productivity and quality of stone mistletoe (Begonia sp.) plants; one method is the application of liquid organic fertiliser made from gamal leaves. This study aimed to determine the effect of the concentration of liquid organic fertiliser made from gamal leaves on the growth of stone mistletoe cuttings. This study employed a Randomised Block Design (RBD) with a single factor comprising six treatment levels and three replicates. The concentrations used were as follows: K0: Control, K1: 40 ml/l water, K2: 80 ml/l water, K3: 120 ml/l water, K4: 160 ml/l water and K5: 200 ml/l water. The observational data were analysed using analysis of variance (ANOVA), and where a significant effect was found, this was followed by a BNJ test at the 5% significance level. The results of the study showed that treatment K3 (120 ml/litre of water) had the most favourable effect on all observed variables, namely shoot length, number of leaves, leaf length, leaf width and root length.